Effect of Feeding Fruit and Vegetable Wastes on Growth and Protein Content of BSF Maggot (Hermetia illucens): Pemberian Pakan Sampah Buah dan Sayur terhadap Pertumbuhan dan Kadar Protein Maggot BSF (Hermetia illucens) - Ananda, Resti; Johan, Henny; Nursaadah, Euis; Ruyani, Aceng; Harlita (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
Black Soldier Fly maggot can reduce the amount of organic waste, especially fruit and vegetable wastes. Its break down organic waste into its food containing very high protein, so it become a promising animal feed. This study aimed to analyze effect of feeding tomato fruit waste and mustard vegetable waste on the growth and protein content of BSF maggot (Hermetia illucens). This study applied a complete randomized design (CRD) with 5 treatments (different percentages of tomato and mustard vegetable wastes) and 3 replications. The growth parameters measured were mass, length, thickness of BSF maggot which were analyzed statistically using the ANOVA test and continued with the Least Significant Difference (LSD) test. Protein content was analyzed using the automatic Kjeldahl test. Our results showed that feeding fruit and vegetable wastes have a significant effect on growth (mass, length, thickness) and maggot protein levels. It can be concluded that feeding fruit and vegetable wastes affect the growth (mass, length, thickness) and protein content of BSF maggot. Key words: growth, maggot, mustard waste, protein, tomato waste